2017
DOI: 10.1109/twc.2017.2671869
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Subarrays for Hybrid Precoding in Wideband mmWave MIMO Systems

Abstract: Hybrid analog/digital precoding architectures can address the trade-off between achievable spectral efficiency and power consumption in large-scale MIMO systems. This makes it a promising candidate for millimeter wave systems, which require deploying large antenna arrays at both the transmitter and receiver to guarantee sufficient received signal power. Most prior work on hybrid precoding focused on narrowband channels and assumed fully-connected hybrid architectures. MmWave systems, though, are expected to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
412
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 401 publications
(431 citation statements)
references
References 34 publications
3
412
0
Order By: Relevance
“…[21] proposes a limited feedback for channel state information (CSI) and presents a hybrid analog-digital beamforming codebook design for wideband case. Some other solutions to further reduce the cost of hardware or feedback, such as dynamic partially-connected structure or low-resolution hybrid beamforming have also been considered in [19], [22], [23]. Now with the emergence of RIS, beamforming becomes more flexible and controllable.…”
Section: Introductionmentioning
confidence: 99%
“…[21] proposes a limited feedback for channel state information (CSI) and presents a hybrid analog-digital beamforming codebook design for wideband case. Some other solutions to further reduce the cost of hardware or feedback, such as dynamic partially-connected structure or low-resolution hybrid beamforming have also been considered in [19], [22], [23]. Now with the emergence of RIS, beamforming becomes more flexible and controllable.…”
Section: Introductionmentioning
confidence: 99%
“…A useful criterion for hybrid codebook construction was also developed in [20], where both the baseband and radio frequency (RF) precoders are taken from quantized codebooks. Following [20], [21] considered the dynamic subarrays architecture for wideband hybrid beamforming, where a criterion for constructing the optimal subarrays that maximize the spectral efficiency was proposed. Furthermore, [22] showed that hybrid beamforming with a small number of RF chains can asymptotically approach the performance of fully digital beamforming for a sufficiently large number of transceiver antennas.…”
Section: Introductionmentioning
confidence: 99%
“…Since the array size of the massive MIMO system is typically large, digital precoding becomes more complex in terms of area, cost, and power limitations. But the hybrid precoder architecture shown in Figure 1 groups the transmitting antenna elements into a number of subarray modules [10]. Hence, separate RF chains are assigned for each subarray module rather than individual antenna element which reduces the cost of the system considerably.…”
Section: Introductionmentioning
confidence: 99%
“…The digital precoder controls the signal supplied to the RF precoder by the complex weight matrix W D , and the complex analog weight matrix W A of the RF precoder controls the phase shift network of the antenna array. More extensive research works have been carried out on developing hybrid precoding algorithms in [9][10][11][12]. All these works devise various hybrid algorithms for massive antenna systems based on computationally intensive block diagonalization and eigenvalue decomposition methods.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation